2004
DOI: 10.1111/j.1365-2796.2004.01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inflammatory attacks in the classical type hyper‐IgD syndrome on immunoglobulin D, cholesterol and parameters of the acute phase response

Abstract: Methods. Blood samples were drawn during and in between febrile attacks, and concentrations of C-reactive protein (CRP), ferritin, procalcitonin,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 32 publications
1
11
0
6
Order By: Relevance
“…7 In general, a strong acutephase response is seen with significantly elevated C-reactive protein, sometimes combined with elevated levels of interleukin-1, interleukin-6, and tumor necrosis factor in serum. 4,8 Infants and young children with fever of unknown origin are frequently referred to hospitals for diagnostic evaluation. The differential diagnosis is broad, and the diagnosis of MKD can be challenging.…”
mentioning
confidence: 99%
“…7 In general, a strong acutephase response is seen with significantly elevated C-reactive protein, sometimes combined with elevated levels of interleukin-1, interleukin-6, and tumor necrosis factor in serum. 4,8 Infants and young children with fever of unknown origin are frequently referred to hospitals for diagnostic evaluation. The differential diagnosis is broad, and the diagnosis of MKD can be challenging.…”
mentioning
confidence: 99%
“…Understandably, many pediatricians are concerned about the recurrence of febrile episodes in children with MKD; these episodes need to be distinguished by true infections. One study of the acute phase response in MKD patients experiencing a febrile attack showed that elevated CRP levels with a procalcitonin concentration less than 2 nglmL was indicative of a febrile attack without any bacterial involvement (33).…”
Section: Diagnosing Mkdmentioning
confidence: 99%
“…Развитие спаечного процесса в брюшной полости говорит о том, что боли в животе во время лихорадочных приступов связаны с асептиче-ским перитонитом. Следует обратить внимание на то, что в редких случаях даже в межприступный период полной ремиссии симптомов не отмечается, на лабо-раторном уровне это проявляется в виде повышения уровня маркеров воспаления [7,8].…”
Section: клинические проявления и диагностика синдромаunclassified
“…В настоящее время при-нято считать, что повышение уровня иммуноглобулина D в плазме крови не является специфическим маркером синдрома периодической лихорадки с дефицитом мева-лонаткиназы [11]. У большинства больных помимо имму-ноглобулина D повышается уровень иммуноглобулина А (более 260 мг/дл) и иммуноглобулина М [12].…”
Section: клинические проявления и диагностика синдромаunclassified
See 1 more Smart Citation